2001
DOI: 10.4049/jimmunol.167.9.4791
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CCR4 Mediates Antigen-Primed T Cell Binding to Activated Dendritic Cells

Abstract: The binding of a T cell to an Ag-laden dendritic cell (DC) is a critical step of the acquired immune response. Herein, we address whether a DC-produced chemokine can induce the arrest of T cells on DC under dynamic flow conditions. Ag-primed T cells and a T cell line were observed to rapidly (∼0.5 s) bind to immobilized DC at low shear stress (0.1–0.2 dynes/cm2) in a pertussis toxin-sensitive fashion. Quantitatively, Ag-primed T cells displayed 2- to 3-fold enhanced binding to DC compared with unprimed T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…We hypothesized that Ag-presenting DCs may be involved as others and we have detected CCR4 expression among DCs (34,35). It has been reported that CCL22 is chemotactic for myeloid DCs (40), promotes Ag-activated T cell binding to DCs (41), and permits formation of DC-T cell clusters in secondary lymphoid tissues and inflammatory sites (36). Indeed, our coculture studies demonstrated impaired IFN-␥ production when CCR4 ϩ/ϩ T cells were cultured with CCR4 Ϫ/Ϫ DCs, suggesting that CCR4 is necessary for optimal interaction of CD4 ϩ T cells and APCs to promote an anamnestic Th1-mediated response to mycobacterial PPD.…”
Section: Discussionmentioning
confidence: 87%
“…We hypothesized that Ag-presenting DCs may be involved as others and we have detected CCR4 expression among DCs (34,35). It has been reported that CCL22 is chemotactic for myeloid DCs (40), promotes Ag-activated T cell binding to DCs (41), and permits formation of DC-T cell clusters in secondary lymphoid tissues and inflammatory sites (36). Indeed, our coculture studies demonstrated impaired IFN-␥ production when CCR4 ϩ/ϩ T cells were cultured with CCR4 Ϫ/Ϫ DCs, suggesting that CCR4 is necessary for optimal interaction of CD4 ϩ T cells and APCs to promote an anamnestic Th1-mediated response to mycobacterial PPD.…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that the increased adhesion of naive T cells to mature DCs is not an exclusive consequence of the increased ability of mature DCs to activate naive T cells. Expression of different adhesion receptors (31,32), of chemokines (33), and changes in mobility and cytoskeleton (20) probably all concur to efficient adhesion of mature DCs to naive T cells. We previously showed that, in this model, only a 2-to 3-fold difference in the efficiency of naive T cell stimulation was found between wild-type and CD80/86-deficient mature DCs (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is also a potent chemoattractant for additional cell types, including DCs (10,24). MDC produced by DCs attracts CCR4-bearing activated (or memory) T cells to enhance immune responses and increase effector functions (54), and it may allow for T cell-B cell interaction, with the subsequent formation of germinal centers (47). Immunization with these recombinant viruses resulted in the expression of the intended molecules and significantly more recruitment and/or activation of DCs, B cells, and T cells to the site of immunization than did immunization with the parent virus, particularly at 3 dpi, as shown by the expression of markers for each of the immune cell types.…”
Section: Discussionmentioning
confidence: 99%